Inibidor bidirecional de eventos de runaway no comutador de tap de reguladores de tensão em redes de distribuição reconfiguráveis com geração distribuída - SOUZA, Vanderson Carvalho de (Universidade Federal do Pará, 2024)
Climate change has intensified over the years, especially as a result of the global energy model that is predominantly based on the use of fossil fuels. Thus, there is an urgent need to boost a low-carbon economy as a response to the climate crisis. In this context, renewable energy sources emerge as the main alternative to fossil fuels. However, the integration of these sources into distribution networks can cause voltage control problems resulting from bidirectional power flow in such networks. An important voltage control problem is the phenomenon known as tap changer runaway condition in step-voltage regulators (SVRs). Nowadays, the problem is further challenging in reconfigurable distribution networks with renewable energy sources connected to both the source-side and load-side of the SVR. This problem occurs when the SVR control cannot adequately distinguish the origin of the active power flow through the SVR and tries to control the voltage on the side of the network with the highest short circuit capacity (strong side), causing under or overvoltage on the side of the network with the lowest short circuit capacity. short circuit (weak side). Current solutions to mitigate the runaway problem are mainly based on three categories: 1) voltage control support by distributed generation (DG); 2) use of remote measurements/information; and 3) use of local measurements/information. However, considering practical aspects, only solutions in the third category are feasible. Even so, these solutions are restricted to application for inhibiting the runaway condition caused exclusively by reverse power flow. In this Thesis, an algorithm is proposed for robust local bidirectional on-line inhibition of the runaway condition based only on a test tap switching with robustness guarantees and without the need for switching of tap test coordinate in cascaded SVRs. The main contributions of the Thesis are the innovative application of the algorithm in robust local bidirectional on-line inhibition of the runaway condition in the tap switch and the introduction to industrial insights. The accuracy and robustness of the proposed algorithm are verified through time series power flow simulations carried out on two test networks, with noise and gross errors in measurements, using extensive Monte Carlo simulations. The uncoordinated operation of test tap switching in cascaded SVRs is examined through case studies on a long real rural distribution network. Finally, the effect of photovoltaic (PV) source variability on the performance of the proposed algorithm is evaluated. The results obtained confirmed the effectiveness of the proposed algorithm in bidirectional inhibition of the runaway condition